Overview of Student Skills in Performing a Combination of Effleurage Massage Techniques and Slow Deep Breathing to Reduce Menstrual Pain - Dini Ariani; Hani Septiani; Wita Solama (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: In general the treatment of menstrual pain is divided into two categories, pharmacology and non-pharmacology. Non pharmacological pain management is safer to use because it does not cause side effects like drugs because non pharmacological therapy uses physiological processes. One of the non pharmacological pain management is a combination of effleurage massage technique and slow deep breathing. Massage effleurage is a movement using the entire surface of the hand that is rubbed lightly and soothingly. This technique aims to improve blood circulation, reduce pain, and stretch muscles as well as promote physical and mental relaxation. Dysmenorrhea that never goes away makes medical personnel, one of which is physiotherapy, very capable of playing an important role in handling it. The role of physiotherapy in cases of menstrual pain itself or dysmenorrhea is to help provide exercise therapy in the form of deep breathing exercises which are deep breathing techniques with the aim of increasing the amount of oxygen in the body and providing a relaxing effect on the body and education in the form of healthy lifestyle and healthy activities to reduce the consumption of analgesic drugs that have long-term dependency effects. Objective: This study was to describe the combination of effleurage massage technique and slow deep breathing of female students in reducing menstrual pain. to know the description of the combination of effleurage massage technique and slow deep breathing of female students in reducing menstrual pain. Method: This study uses a descriptive research design. The sample in this study was determined using a quota sampling technique, namely as many as 32 respondents who fit the inclusion criteria. Conclusion: most of the respondents were able to do a combination of effleurage massage and slow deep breathing techniques.